FM 2015: Formal Methods: 20th International Symposium, Oslo, Norway, June 24-26, 2015, Proceedings - Bjørner, Nikolaj (Springer, 2015)
This book constitutes the refereed proceedings of the 20th International Symposium on Formal Methods, FM 2015, held in Oslo, Norway, in June 2015. The 30 full papers and 2 short papers presented were carefully reviewed and selected from 124 submissions. The papers cover a wide spectrum of all the different aspects of the use of and the research on formal methods for software development.